Efeito da altura da planta e uso de aditivos na ensilagem do capim BRS Capiaçu - Rafael de Oliveira Lima (2022)
The objective was to evaluate plant height and additives in the silage of Pennisetum purpureum Schum cv. BRS Capiaçu. The experimental design was completely randomized, in a 4x4 factorial scheme, with four plant heights (CA): 2 - 2.5 - 3 - 3.5 meters, control and three additives: homolactic inoculant, heterolactic inoculant and cornmeal as additive. absorbent, with six repetitions. Six experimental PVC microsilos were used for each treatment, which were opened 60 days after the closing of the silo, to determine the silage parameters: density, dry matter recovery (DMR), effluent loss (EL), gas loss (GL) and pH, dry matter (DM), organic matter (OM) and crude protein (CP) content. Data were submitted to analysis of variance and regression. The choice of models was based on the significance of linear and quadratic coefficients, at the level of 5% probability by Tukey's test. No interaction was observed between cutting height x additives (p>0.05) for PG and MO. There was an interaction between height x additives (p<0.05) for density, RMS, PE, pH, MS and CP. The productivity observed at 3.5 meters was 18.64 t ha-1 dry matter, with an interval between cuts of 173 days, similar to the height of 3 meters, which was 18.62 t h-1 of DM with 108 days of interval between polite. The absorbent additive and the height increase were effective to reduce losses, the homolactic additive promoted the best values for pH 3.34 at the height of 2.5 meters. It is recommended to cut the BRS Capiaçu for silage when the plant reaches 2.5 meters in height and use homolactic additive.